2015
DOI: 10.1007/s10620-015-3538-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Gastrointestinal Bleeding After Placement of Continuous-Flow Left Ventricular Assist Device: A Case Series

Abstract: We found a higher GIB rate compared with prior studies. Bleeding events were associated with multiple procedures and interventions. We recommend an algorithmic approach to LVAD patients who bleed. Our experience suggests that PE is warranted at initial presentation in order to achieve hemostasis, prevent recurrent GIB, and decrease subsequent readmission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…[5, 6] CF-LVADS, however, demonstrate an increased incidence of GI bleeding, estimated at 63 events/100 patient years or 20 to 30% [5-7], with recurrent bleeding at 30 to 40%. [4, 8, 9] However, the incidence of bleeding has been reported to be as high as 61% [10] with recurrent bleeding as high as 72% [11]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5, 6] CF-LVADS, however, demonstrate an increased incidence of GI bleeding, estimated at 63 events/100 patient years or 20 to 30% [5-7], with recurrent bleeding at 30 to 40%. [4, 8, 9] However, the incidence of bleeding has been reported to be as high as 61% [10] with recurrent bleeding as high as 72% [11]. …”
Section: Resultsmentioning
confidence: 99%
“…[14] The majority of bleeding events resolve within 4 days and patients require an average of three to four units of packed red blood cells (PRBCs) per bleeding event. [10, 12, 14, 15] Overt, upper GI bleeding is the most frequent presentation with 50% of patients reporting passage of melenic stools. [4, 10, 14]…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7] Of note, similar observations were made in patients on mechanical circulatory support using pulsatile flow pumps (loss of high molecular weight multimers of von Willebrand factor). 8 Notwithstanding, pathophysiology of Heyde syndrome is probably multifactorial (mucosal ischemia, cholesterol embolization, acquired platelet dysfunction and inflammatory reactions).…”
Section: The Authors Respondmentioning
confidence: 99%
“…The authors show that preoperative right-sided congestion may place LVAD recipients at increased risk of developing postoperative hemorrhage. Previous studies have suggested that the lowest chance of bleeding occurred in blood type A patients [12] and the highest in patients with history of GI hemorrhage prior to LVAD placement [11]. Furthermore, male gender and older age are recognizable risk factors [5].…”
mentioning
confidence: 98%
“…Indeed, angioectasias account for the majority of the culprit lesions, with particular predilection to the upper GI tract. We have previously shown that routine use of push enteroscopy in LVAD patients with GI hemorrhage increased diagnostic yield threefold, from 29 to 90%, successfully eradicating lesions and achieving endoscopic hemostasis, potentially decreasing future GI readmission rates [6,11]. Such an algorithm has been subsequently accepted at the institutional level and remains an effective tool in clinical practice.…”
mentioning
confidence: 99%